Epidemiology of Adults Receiving Acute Inpatient Rehabilitation for a Primary Diagnosis of Traumatic Brain Injury in the United States. Issue 2 (March 2015) - Cuthbert, Jeffrey P.; Harrison-Felix, Cynthia; Corrigan, John D.; Kreider, Scott; Bell, Jeneita M.; Coronado, Victor G.; Whiteneck, Gale G.
Abstract : Objective: To estimate the overall and by age-group characteristics at admission and discharge from rehabilitation between 2001 and 2010 of all late-teens and adults undergoing inpatient rehabilitation for a primary diagnosis of traumatic brain injury (TBI) in the United States. Design: Secondary data analysis. Setting: Acute inpatient rehabilitation facilities. Participants: Patients aged 16 years and older receiving inpatient rehabilitation for a primary diagnosis of TBI between 2001 and 2010. Main Outcome Measures: Functional independence, level of disability, and living situation. Results: The incidence of TBI by age group found the largest proportion of cases to be aged 80 years and older, with a gradual decline in incidence in the age group of 30 years, at which point there was a slight increase. Injuries resulted predominantly from falls (49.8%) and motor vehicle crashes (40.8%); however, injuries to the youngest individuals were largely from motor vehicle crashes with decreasing rates as age increased, while injuries due to falls rose as age increased, with the oldest age groups most likely to incur a TBI. Preinjury alcohol misuse and substance use were found to occur in 22.9% and 12.2% of the total population, respectively; however, age distributions demonstrated high preinjury use among individuals younger than 50 years (eg, 46.4% and 30.6% for those aged 20 and 29 years, respectively) with decreasing misuse as age increased. Of the total population, 49.2% were retired, 31.1% employed, 14.1% not working, and 5.6% students. Trends by age showed that younger individuals were more likely to be students or employed (eg, 14.5% and 62.0% for those aged 20 and 29 years, respectively), with employment status peaking for those aged 30 to 39 years, and declining to 3.2% for the oldest age group (80 years and older). The trend of person(s) living alone between pre- and postrehabilitation showed the least amount of change for those aged 16 to 19 years with steadily increasing changes as age increased. Similar trends were seen for residence changes pre- and postrehabilitation, with the youngest most likely to return to living at a private residence, and a gradual decrease in return to living at a private residence as age increased. FIM instrument ("FIM") Motor and Cognitive subscale scores demonstrated that younger individuals had lower scores at admission to rehabilitation and higher scores at rehabilitation discharge. Conclusion: This study provides population estimates for all patients 16 years of age and older receiving inpatient rehabilitation for a primary diagnosis of TBI in the United States between 2001 and 2010. A recent trend shows the aging of the inpatient TBI rehabilitation population. Many characteristics important to rehabilitation outcomes are influenced by age, with older individuals trending toward being female, having less severe TBIs, incurring TBIs as a result of falls, but showing less improvement during rehabilitation, greater resulting disability, and more changes in their living situation postrehabilitation. These findings are of particular interest, as the oldest age groups considered in these analyses did not include the baby boom population. Abstract : Supplemental Digital Content is Available in the Text.